Identification of an epicuticular wax crystal deficiency gene Brwdm1 in Chinese cabbage (Brassica campestris L. ssp. pekinensis) - Song, Gengxing; Liu, Chuanhong; Fang, Bing; Ren, Jie; Feng, Hui (Frontiers in Plant Science, 2023)
Introduction The cuticle wax covering the plant surface is a whitish hydrophobic protective barrier in Chinese cabbage, and the epicuticular wax crystal deficiency normally has higher commodity value for a tender texture and glossy appearance. Herein, two allelic epicuticular wax crystal deficiency mutants, wdm1 and wdm7, were obtained from the EMS mutagenesis population of a Chinese cabbage DH line ‘FT’. Methods The cuticle wax morphology was observed by Cryo-scanning electron microscopy (Cryo-SEM) and the composition of wax was determined by GC-MS. The candidate mutant gene was found by MutMap and validated by KASP. The function of candidate gene was verified by allelic variation. Results The mutants had fewer wax crystals and lower leaf primary alcohol and ester content. Genetic analysis revealed that the epicuticular wax crystal deficiency phenotype was controlled by a recessive nuclear gene, named Brwdm1. MutMap and KASP analyses indicated that BraA01g004350.3C, encoding an alcohol-forming fatty acyl-CoA reductase, was the candidate gene for Brwdm1. A SNP 2,113,772 (C to T) variation in the 6th exon of Brwdm1 in wdm1 led to the 262nd amino acid substitution from threonine (T) to isoleucine (I), which existed in a rather conserved site among the amino acid sequences from Brwdm1 and its homologs. Meanwhile, the substitution changed the three-dimensional structure of Brwdm1. The SNP 2,114,994 (G to A) in the 10th exon of Brwdm1 in wdm7 resulted in the change of the 434th amino acid from valine (V) to isoleucine (I), which occurred in the STERILE domain. KASP genotyping showed that SNP 2,114,994 was co-segregated with glossy phenotype. Compared with the wild type, the relative expression of Brwdm1 was significantly decreased in the leaves, flowers, buds and siliques of wdm1. Discussion These results indicated that Brwdm1 was indispensable for the wax crystals formation and its mutation resulted in glossy appearance in Chinese cabbage.